Importance of DNA and histone methylation in in vitro plant propagation for crop improvement: a review. (2nd March 2016) - Karim, R.; Nuruzzaman, M.; Khalid, N.; Harikrishna, J.A.
Abstract: Epigenetic changes including DNA and histone methylation may reorganise the nuclear architecture during in vitro culture. The states of methylation resulting from in vitro cultures are often related to control the somatic embryogenesis and regeneration process via modulating gene expression. By changing the methylation profile, it is possible to alter gene expression which may be applicable to produce large number of high quality planting materials or to improve agronomic traits leading to crop improvement. Understanding the molecular mechanisms of methylation alterations and acquisition of developmental cell fate during in vitro cultures can help in the development of strategies to enhance the embryogenic capability and totipotency in recalcitrant plant species and genotypes. Moreover, the methylation profile may also be useful to adapt crops under adverse environment as the plants undergo through various stresses during in vitro cultures. In this article, we review the literature on the role of DNA and histone methylation in plant variation and discuss the potential of targeted epigenetic variation for crop improvement.